The Labor-Induced Pregnancy Cases In Dr Soetomo General Hospital: A Descriptive Study - Alfin Firasy (Jurnal Ilmu Kesehatan dan Kesehatan, 2021)
Background: Labor induction is a procedure to stimulate uterine contractions during pregnancy before labor begins on its own to achieve a vaginal birth with medical or mechanical intervention to start the labor. This procedure aims to stimulate more extensive contraction in the uterus. The labor induction can reduce the caesarean rate. Prostaglandin E2 (PGE2) and misoprostol are the commonest medicine used to ripen the cervix in the Dr. Soetomo Hospital. Objective: Our study aim to evaluate the success rate of induction of labor patient. Methods: This study was a descriptive study using the medical record in 2018 in the Dr. Soetomo General Hospital, Surabaya. A total of 183 patient’s medical record data who underwent induced labor were used in this study. Inclusion criteria were the women with indication to deliver and have no cephalo-pelvic disproportion. Women with contraindication labor induction were excluded. Data was described using table and narrative approach. Results: The most range of gestational age was 21-36 weeks (53.01%) followed by 37-42 weeks (42.07%). There were 68 patients (37,1%) primigravida and 115 patients (62,8%) were multipara. The major induced labor was conducted with misoprostol (78.6%), and the most pelvic scores were 2 (58.46%) before underwent induced labor. Vertex delivery was the preferred mode of delivery after the induction of labor with 89 patients (48,62%). The labor induction failure followed with the caesarean operation were 27 patients (14,7%) and one patient (0,54%) with hysterotomy, most of them caused by failure to progress and fetal distress. There were 78 babies (43%) with the weight over 2500 g, 28 babies (31%) were over 2000 g, and the other was below 2000 g. A total of 84.71% with labor induction can be delivered vaginally, and It is a good number to reduce the rate of caesarean operations. Conclusion: This study concludes that misoprostol uses for the induction of labor than the other. Delivery abdominal is less percentage than the additional delivery finds that as a failure of induction of labor. The Labor induction success to delivered vaginally can reduce the rate of caesarean operation.